Evaluating a digital prehabilitation tool in patients with colorectal surgery: protocol for a multisite randomised controlled trial - George J Chang; Emily Finlayson; Cindy Kin; Kelsey Ogomori; Jeanette Broering; Camille Rogine (BMJ Open)
Introduction Colorectal cancer is a leading cause of cancer mortality in the USA and occurs most frequently in older adults. These patients are at increased risk of adverse outcomes following major cancer surgery. While prehabilitation has been shown to mitigate this risk, multiple barriers to implementation remain. Our team created a digital tool co-designed with older adults that employs an algorithm to assess patient-specific geriatric vulnerabilities and generate personalised prehabilitation programmes before surgery.Methods and analysis We have designed a multisite, unblinded randomised trial to be completed at three high-volume academic cancer centres located in California or Texas. Our study population is individuals aged 65 and older with planned colorectal cancer resection who are proficient in English and have home internet access. We aim to enroll 132 patients who will be randomised in a 2:1 ratio to receive the intervention (assistance from a home health coach and access to the web application (web app)) or control (usual care with written prehabilitation materials). Our primary outcome is patient engagement with prehabilitation activities.Ethics and dissemination A properly executed, written, informed consent will be obtained from each subject prior to entering the subject into the trial. Information will be given in both oral and written form, and subjects may withdraw at any time from the study without effect on their medical care. The protocol and consent form have been approved by the Institutional Review Board (IRB) of each participating centre. We anticipate publication of results in a peer-reviewed journal.Trial registration number NCT05520866.